Lateral Patellar Dislocation: A Critical Review and Update of Evidence-Based Rehabilitation Practice Guidelines and Expected Outcomes. Issue 5 (5th May 2022) - Watson, Richard; Sullivan, Breanna; Stone, Austin V.; Jacobs, Cale; Malone, Terry; Heebner, Nicholas; Noehren, Brian
Abstract : » Nonoperative treatment of a lateral patellar dislocation produces favorable functional results, but as high as 35% of individuals experience recurrent dislocations. » Medial patellofemoral ligament reconstruction is an effective treatment to prevent recurrent dislocations and yield excellent outcomes with a high rate of return to sport. » Both nonoperative and postoperative rehabilitation should center on resolving pain and edema, restoring motion, and incorporating isolated and multijoint progressive strengthening exercises targeting the hip and knee. » Prior to return to sports, both functional and isolated knee strength measurements should be used to determine leg symmetry strength and to utilize patient-reported outcome measures to assess the patient's perceived physical abilities and patellofemoral joint stability.